2016
DOI: 10.3390/md14060106
|View full text |Cite
|
Sign up to set email alerts
|

Metals of Deep Ocean Water Increase the Anti-Adipogenesis Effect of Monascus-Fermented Product via Modulating the Monascin and Ankaflavin Production

Abstract: Deep ocean water (DOW) obtained from a depth of more than 200 m includes abundant nutrients and minerals. DOW was proven to positively increase monascin (MS) and ankaflavin (AK) production and the anti-adipogenesis effect of Monascus-fermented red mold dioscorea (RMD). However, the influences that the major metals in DOW have on Monascus secondary metabolite biosynthesis and anti-adipogenesis remain unknown. Therefore, the major metals in DOW were used as the culture water to produce RMD. The secondary metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…High fat diet (HFD) supplemented with the amine derivatives of monascus pigments, 4- phenylbutylamine (PBA) (2.5 µM), and 2-(p-toyly) ethylamine (TEA) (12.5µM) have demonstrated an inhibitory activity against adipogenic differentiation in 3T3-L1cells [128]. Metals present in deep ocean water are found to cause synergistic effects on the production of monascin and ankaflavin, and DOW with RMD shows a significant anti-adipogenesis effect [131].…”
Section: Uses Of Microbial Pigmentsmentioning
confidence: 99%
“…High fat diet (HFD) supplemented with the amine derivatives of monascus pigments, 4- phenylbutylamine (PBA) (2.5 µM), and 2-(p-toyly) ethylamine (TEA) (12.5µM) have demonstrated an inhibitory activity against adipogenic differentiation in 3T3-L1cells [128]. Metals present in deep ocean water are found to cause synergistic effects on the production of monascin and ankaflavin, and DOW with RMD shows a significant anti-adipogenesis effect [131].…”
Section: Uses Of Microbial Pigmentsmentioning
confidence: 99%
“…In recent years, the secondary metabolites of red mold rice have been studied to further explore their functional compounds. Among them, the yellow pigments monascin (MS) and ankaflavin (AK) are proven as the functional compounds for the prevention of cardiovascular disease, fatty liver, and lipogenesis ( Figure 1 ) [ 9 , 10 , 11 ]. Furthermore, both MS and AK can achieve anti-inflammatory effects by reducing inflammatory factor levels [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies on the effect of minerals on Monascus yellow pigment production have been conducted using spectrophotometric analysis, 12,13,27 few studies have been concerned with specific monascin production analysis. Lung et al 33 have reported that the addition of Mg, Ca, Zn, or Fe to water increased monascin production when dioscorea was subjected to solid-state fermentation with M. purpureus. However, for monascin production of M. ruber NBRC 32318, the Ca and Mg in SMUF II showed no effect, or rather canceled the stimulation effect of SMUF I to yield production levels equal to the whole SMUF.…”
Section: Discussionmentioning
confidence: 99%